Production potential of annual meadows in Moroccan coastal region - Kallida R.; Shaimi N.; Souihka A. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Harsh soils of the coastal middle region of Morocco are less favorable and over-exploited areas. They are managed as traditional extensive systems, which raise problems of profitability of the production and the durability of the ecological system. Diversification and adaptation of fodder resources is one way to improve and increase forage productions. The aim of this study is to test the performance of production and the adaptation of the some forage species in mixture stands. Four meadows, containing mainly annual species of fodder grasses and legumes were sown in a site located the middle coastal region of Morocco. Meadows were exploited by forage cutting the first year, and by grazing in the beginning of cycle and later mowing for hay on the second year. Dry matter yields ranged from 7 to 12 t ha-1 with differences in meadows production. The based fast growth species meadow had exceeded the others by about 5 t/ha of dry matter. Despite some inconveniences of the beginning of cycle, yields were satisfying. There was no elimination of species since all sown species were present in the harvest.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)